The biotic effects of climate change - Lister, Adrian M (Clin Med (Lond), 2009)
Humans are part of the biosphere and dependent upon it. The impact of climate change on ‘ecosystem services’ is therefore of extreme concern. Many studies demonstrate unequivocally that global warming is shifting the distribution of animal and plant species, affecting the composition not only of natural ecosystems but of agricultural ones as well, and also altering the range and impact of pathogenic organisms. The future trajectory of such complex processes is hard to map accurately, but even conservative estimates predict substantial species extinctions and changes in regional productivity. There is still a chance to significantly mitigate these effects, however, if urgent measures are taken. The biotic effects of climate change are strongly exacerbated by ongoing habitat destruction, which no less urgently needs to be halted or reversed by concerted international action. In terms of its rate and its human causation, the present crisis is not analogous to past ‘natural’ events.